Tithes in the Long 10th Century: The Example of the Dioceses of Freising and Mâcon - Patzold, Steffen (Frühmittelalterliche Studien, 2023)
This article explores the question of how tithing rights in the dioceses of Freising and Mâcon developed between the ninth and eleventh centuries. I argue contrary to previous research that in these two dioceses, the tithes at local churches did not fall into the hands of the laity already in the Carolingian period, based on ideas of ‘Eigenkirchenrecht’. Instead, we can observe how, from the later ninth century onwards, bishops themselves detached tithing rights from baptismal churches and allocated them to other, minor churches, to foster them economically. In the course of the tenth century, bishops then also gave tithing rights - without any church - to laymen, in Freising at first usually in the context of exchanges. In the second half of the eleventh century, in documents from the diocese of Mâcon, tithes in lay hands were usually presented as a sinful result of alienation; they were ‘returned’ to the cathedral (or bought back by the bishops). In the course of this, however, tithing rights that actually had been allocated to baptismal churches in the ninth century, now passed into the hands of the cathedral chapter or the bishop.